Relationship between the spread of coronavirus disease 2019, social frailty and depressive symptoms in patients with heart failure. (11th May 2022) - Shakuta, S; Yamashita, M; Kamiya, K; Hamazaki, N; Nozaki, K; Uchida, S; Noda, T; Ueno, K; Maekawa, E; Yamaoka-Tojo, M; Matsunaga, A; Ako, J
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): the Japan Society for the Promotion of Science (JSPS) KAKENHI Background: Owing to the spread of coronavirus disease 2019 (COVID-19), people have refrained from going out unnecessarily and have been maintaining social distance. These new lifestyle approaches have affected people physically, psychologically, and socially. Patients with heart failure (HF) are more likely to have social frailty, physical frailty, cognitive impairment, and depressive symptoms, and an overlap of these conditions leads to adverse events. Therefore, multi-domain assessment and understanding of the condition of patients with HF are important for disease management. The spread of COVID-19 is a predicted risk factor for these events, but its impact in patients with HF has not been investigated. Purpose: We investigated whether the spread of COVID-19 is associated with the development of the multi-domain of frailty in patients with HF. Methods: Patients who were independent in their daily activities before admission were included in the study. The presence of social frailty (Makizako's five items), physical frailty (Fried phenotype model), cognitive impairment (Mini-Cog), and depressive symptoms (the Patient Health Questionnaire-2) in patients with HF were assessed at hospital discharge. Logistic regression analyses were used to examine the impact of the spread of COVID-19 on the development of the multi-domain of frailty in patients with HF. Results: We included 482 patients in this study. Median patient age was 74 years, and 64.5% were male. In multivariate logistic regression analyses, the spread of COVID-19 was significantly associated with the development of social frailty (odds ratio [OR]: 1.15, 95% confidence interval [CI]: 1.02–1.30) and depressive symptoms (OR: 1.14, 95% CI: 1.02–1.27) but not with the development of physical frailty (OR: 1.24, 95% CI: 0.51–3.02) and cognitive impairment (OR: 1.72, 95% CI: 0.80–3.73). Conclusion: The spread of COVID-19 was associated with the development of social frailty and depressive symptoms in patients with HF. Evaluation of social frailty and depressive symptoms during hospitalization would support disease management and understand their social and psychological conditions specific to the spread of COVID-19.